Molecular characterization of a phytoplasma of the ash yellows group occurring in strawberry (Fragaria x ananassa Duch.) plants in Argentina - Fernandez, Franco Daniel (2013)
Strawberry (Fragaria x ananassa Duch. cv. Camino Real) plants showing phyllody symptoms were detected in production fields in Bella Vista (Corrientes province, Argentina). DNA from all symptomatic samples analyzed yielded fragments of the expected size in PCR reactions using phytoplasma universal primers. DNA from asymptomatic plants yielded no products. The associated phytoplasma was designated as Argentinean Strawberry Phyllody (ASP). The ASP sequence of the 16S rRNA gene showed 99–98% homology with members of the 16SrVII ash yellows group. The putative RFLP profile was indistinguishable from the Argentinean alfalfa witches’ broom (ArAWB) phytoplasma. The phylogenetic analysis of nearly full-length 16S rDNA sequence and 16S-23S spacer region yielded a consensus tree wherein ASP clustered into the ash yellows group (16Sr VII) with high confidence values (95), generating a separated branch (100 bootstrap value) together with ArAWB (16Sr VII-C). In Argentina, the 16Sr VII group was also detected in alfalfa (Medicago sativa L.) crops, and weeds [Artemisa annua L. and Conyza bonariensis (L.) Cronquist]. To our knowledge, this is the first report of a phytoplasma from the 16Sr VII group affecting strawberries in Argentina and worldwide